L’immagine delle campagne daciche traianee e di Decebalo in Plinio il Giovane, Ep., 8. 4. 2 (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
In this brief paper, which is limited to the simple purpose of synthesis and clarification, we aim to illustrate the characteristics of the overall image of Decebalus and the Dacian campaigns led by Trajan (101/2; 105/6 AD) that Pliny the Younger has given us, especially in Ep., 8. 4. 2 (dated to 107 AD, just at the end of the emperor's second Dacian campaign). This image can be easily compared, among other things, with some passages from his Panegyric to Trajan (delivered earlier, in 100 AD, but published after the revision, perhaps in 102 or 103 AD). This image will be inserted into the overall framework offered to us by Greco-Roman literary sources on the theme of Trajan's Dacian campaigns. Despite the scarcity of such sources on the subject, it is nevertheless possible to find a common element, characterizing the way in which the Dacian war was represented and perceived in the Roman world: the insistence on the difficulty of the clash and on the value of Decebalus – perceived by Pliny as an enemy who caused his own misfortunes, however brave – together with that on the engineering and technical prowess demonstrated by the Romans, such as to tame the wild and inaccessible nature of Dacia, and with it its inhabitants.